(untitled) (Islas, 2023)
Introduction: The paper analyzes the nominal forms of address (NFA) used towards black individual in notarial documents of the 18th and 19th centuries in Eastern Cuba, extracted from the DONOC corpus. Methods: Methods derived from historical sociolinguistics and politeness theory based on criteria of Brown and Gilman, are applied, and comparison is established with the works of M. Coll and E. Rigatuso. Results: The NFA used to refer to this population in the studied documents are generic and individualizing references. Only in one case was a collective reference found. Conclusions: The studied NFA are an expression of asymmetrical power axis, even in cases where the owners free black individuals. There were similarities with the works of M. Coll and E. Rigatuso, serving as contrasting references in Hispanic-American context.